Personal and sports variables and injuries in handball players: A descriptive analysis - Aurelio Olmedilla Zafra; Amador Blas Redondo; María Laguna Tudela (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract The aim of this work is to relate some of the personal variables (age and experience) and sports (post game, sport category) more important with injuries to players of handball. The study sample consisted of 100 handball players, with a mean age of 23.92 years (+ 5.21), of which 80% ASOBAL (Association Handball clubs in Spain) competed in the league, and the other 20% did so between first and second division. For the evaluation of the variables using a self-report questionnaire in two parts: the first data is collected and sports personality variables, and the second will collect data on sports injuries. The results of this study indicate that the players suffer more injuries on average 2 in a season, with these minor fractures, muscle and tendinitis, being the player's quinces ASOBAL more is injured. The pivots and lateral suffer more injuries than the rest, and the porters seem to have a significantly lower tendency to injure anyone else. The older the greater the likelihood of injury. The completion of jobs that can determine the exact weight of each variable in the injury, which would be very important from prevention, and the performance of their own coaches. Key words: Sports injuries, handball, age, experience, post game, sport category